2213. Etiology of Community-Acquired Pneumonia (CAP) in Hospitalized Native American Adults - Hammitt, Laura (Open Forum Infect Dis, 2019)
BACKGROUND: Native Americans experience a high burden of community-acquired pneumonia (CAP). Thirteen-valent pneumococcal conjugate vaccine (PCV13) was introduced for adults ≥65yrs in 2014. Data on CAP etiology can guide prevention and treatment. METHODS: We enrolled adults hospitalized with CAP and age-group-matched non-hospitalized controls on Navajo and White Mountain Apache tribal lands. Nasopharyngeal/oropharyngeal (NP/OP) swabs from cases and controls were tested by multiplex PCR for respiratory pathogens. Urine from cases and controls was tested for pneumococcus (Sp) by conventional (BinaxNOW) and serotype-specific urine antigen detection (UAD) for 24 serotypes (PCV13 types plus 2, 8, 9N, 10A, 11A, 12F, 15B, 17F, 20, 22F, 33F). Blood culture and chest radiographs (CXRs) were obtained from cases at the provider’s discretion. Radiographic pneumonia was determined by clinical interpretation of CXRs. RESULTS: From March 2016 to March 2018, we enrolled 580 CAP cases with CXR confirmation and 411 controls. Positive blood culture was identified in 42/483 (9%), of which 29 (69%) were Sp. Sp was detected in 164/572 (29%) cases (table). Of 125 cases with serotype information available, serotypes 3 (n = 35; 28%) 8 (n = 19; 15%) and 20 (n = 15; 12%) were the most common. Among 53 Sp cases aged ≥65 years, 26 (49%) were PCV13-type. Compared with blood culture, UAD was 100% sensitive and 100% concordant (n = 24). Viruses were detected by NP/OP PCR in 43% of CAP cases and 18% of controls. Influenza A, parainfluenza type 3, rhinovirus, and RSV were statistically significantly associated with case status. Among 263 cases in whom all diagnostic tests were collected, 63% had a pathogen detected: bacteria alone in 19%, viruses alone in 23%, and both bacterial and viral infection in 22%. Bacterial causes outnumbered viral causes when adjusting for virus detection in the control population. CONCLUSION: Pneumococci were the most common etiology identified among Native American adults with CAP. UAD improved detection of pneumococcal CAP. Respiratory viruses also contributed substantially to CAP burden. Broader prevention strategies, including new vaccines, are required to prevent viral pneumonia and pneumococcal pneumonia caused by serotypes not contained in currently-available vaccines. [Image: see text] DISCLOSURES: All authors: No reported disclosures.